Pharmacokinetic functions of human induced pluripotent stem cell-derived small intestinal epithelial cells - Kabeya, Tomoki; Mima, Shinji; Imakura, Yuki; Miyashita, Toshihide; Ogura, Izumi; Yamada, Tadanori; Yasujima, Tomoya; Yuasa, Hiroaki; Iwao, Takahiro; Matsunaga, Tamihide (Drug metabolism and pharmacokinetics, 2020)
To develop a novel intestinal drug absorption system using intestinal epithelial cells derived from human induced pluripotent stem (iPS) cells, the cells must possess sufficient pharmacokinetic functions. However, the CYP3A4/5 activities of human iPS cell-derived small intestinal epithelial cells prepared using conventional differentiation methods is low. Further, studies of the CYP3A4/5 activities of human iPS-derived and primary small intestinal cells are not available. To fill this gap in our knowledge, here we used forskolin to develop a new differentiation protocol that activates adenosine monophosphate signaling. mRNA expressions of human iPS cell-derived small intestinal epithelial cells, such as small intestine markers, drug-metabolizing enzymes, and drug transporters, were comparable to or greater than those of the adult small intestine. The activities of CYP3A4/5 in the differentiated cells were equal to those of human primary small intestinal cells. The differentiated cells had P-glycoprotein and PEPT1 activities equivalent to those of Caco-2 cells. Differentiated cells were superior to Caco-2 cells for predicting the membrane permeability of drugs that were absorbed through a paracellular pathway and via drug transporters. In summary, here we produced human iPS cell-derived small intestinal epithelial cells with CYP3A4/5 activities equivalent to those of human primary small intestinal cells. [Display omitted]